A CONTRASTIVE STUDY ON JAPANESE AND TURKISH ASPECT: FOCUS ON –TE I-RU AND –(I)YOR - Aytemis DEPCİ (Fırat University, 2019)
The Japanese auxilary construction –te i-ru and Turkish –(I)yor reflect the category of aspect – a gramatical category seen in conjugations. The current study attempts to compare the Japanese aspect marker –te i-ru and its counterpart in Turkish –(I)yor. This article focuses on the distinctions between these two morphemes as well as the similarities by taking into consideration of their semantic features. Various lexical verb categories have been adapted including verb categories of Vendler’s, Mourelatos’, Kindaichi’s and Johanson’s. These categories were compared with each other to eliminate the lacking parts. Examining these four categories, it is aimed to show that with which verb categories both –te i-ru and –(I)yor morhemes are acceptable and denote the same aspectual meaning whereas with some other verb groups they behave differently. Considering to discuss the different senses of –tei-ru and –(I)yor will shed much light on some other interesting points, different semantic features have been analyzed to determine the different meanings of –te i-ru and –(I)yor morphemes. This study proposes both –te i-ru and –(I)yor forms denote ‘progressive’ and ‘habitual’ senses in common, despite the fact that various meanings are also available by these forms. An imperfective marker -te i-ru covers the meaning of progressive, resultative, perfect or habitualness while –(I)yor refers to progressive meaning and habitualness. The progressive perfect meaning can be applied to–(I)yor, as long as durativity is concerned (but not as long as termination is concerned). Other than these meanings, –(I)yor also covers the meaning of futurate, presumptive, historical present (HP), ability and imperative which -te i-ru does not denote.